Workplace Bullying: Dampaknya pada Turnover Intention Karyawan Rumah Sakit di Nusa Tenggara Barat - Ni Wayan Adelia Mutiara Asri; Tifani Dame Hasany; Dinis Cahyaningrum; Dhanny Safitri; Isra Dewi Kuntary Ibrahim (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Abstract: This study aims to analyze the effect of workplace bullying on turnover intention among healthcare employees in a hospital located in West Nusa Tenggara. Using a quantitative approach with a census sampling technique, all 43 employees in the population were included as respondents. The population refers to the entire group of individuals who possess specific characteristics relevant to the research objectives and are selected for analysis to obtain empirical findings. Data were collected using a structured questionnaire and analyzed through linear regression to examine the relationship between workplace bullying and turnover intention. The results indicate that workplace bullying has a positive and significant effect on turnover intention, as evidenced by a t-test significance value of 0.000. These findings confirm that the higher the level of bullying experienced by employees, the greater their tendency to consider leaving their jobs. In the hospital context, intimidation or mistreatment from colleagues or supervisors can trigger stress, reduce motivation, and create psychological discomfort that ultimately increases employees’ intention to resign. Therefore, workplace bullying emerges as a critical factor influencing employees’ decisions to stay or leave the organization. This study highlights the importance of implementing preventive and corrective measures to mitigate bullying and retain competent healthcare personnel to maintain organizational stability.